2009
DOI: 10.1631/jzus.b0820256
|View full text |Cite
|
Sign up to set email alerts
|

Mycoplasma lipoproteins and Toll-like receptors

Abstract: Mycoplasmas, the smallest free-living, self-replicating bacteria with diameters of 200 to 800 nm, have been reported to be associated with human diseases. It is well known that the mycoplasma lipoprotein/peptide is able to modulate the host immune system, whose N-terminal structure is an important factor in inducing immunity and distinguishing Toll-like receptors (TLRs). However, there is still no clear elucidation about the pathogenic mechanism of mycoplasma lipoprotein/peptide and the signaling pathway. Some… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 75 publications
0
28
0
2
Order By: Relevance
“…1c). Mycoplasma lipoprotein lipid moieties are known to be potent immunostimulators, inducing expression of inflammatory cytokines such as TNF-α, IL-6, and IL-1β following the recognition of their lipid moieties by Toll-like receptor complexes 20 . Given that these cytokines are frequently associated with immunopathology, we hypothesized that sensitization by Mp lipoprotein lipid moieties during vaccination induces VED upon challenge with virulent Mp.…”
Section: Resultsmentioning
confidence: 99%
“…1c). Mycoplasma lipoprotein lipid moieties are known to be potent immunostimulators, inducing expression of inflammatory cytokines such as TNF-α, IL-6, and IL-1β following the recognition of their lipid moieties by Toll-like receptor complexes 20 . Given that these cytokines are frequently associated with immunopathology, we hypothesized that sensitization by Mp lipoprotein lipid moieties during vaccination induces VED upon challenge with virulent Mp.…”
Section: Resultsmentioning
confidence: 99%
“…For this, we checked the expression of early endosomal antigen 1 (EEA1), Rab7 and lysosomal associated marker protein-1 (LAMP-1) proteins, which are the hallmarks of early, late and lysosomal compartments, in THP-1 cells infected with Mtb, Mtb∆LprE, and Mtb∆LprE::LprE strains. It has been shown that recruitment of these marker proteins on endocytic compartments is necessary for the sequential maturation of endosomes and phagolysosome fusion [49,50]. Western blot analysis showed a significant increase in the levels of EEA1, Rab7 and LAMP-1 in Mtb∆LprE infected cells in comparison to Mtb and Mtb∆LprE::LprE infected cells (Fig 7A &B).…”
Section: Lpre Mtb Blocks Phago-lysosome Fusion By Down-regulating Thementioning
confidence: 87%
“…Mycoplasma lipoproteins play a critical role in attachment and are engaged in triggering signalling pathways via Toll-like receptors (TLRs) on eukaryotic cells. Binding of mycoplasma diacylated and triacylated lipoproteins to TLRs induces apoptosis, activates monocytes and macrophages as well as initiate the secretion of proinflammatory substances such as tumour necrosis factor-alpha (TNF-a), nuclear factorkappa B (NF-ƙB) interleukin-1 & 6 (IL-1 and IL-6), chemokines and macrophage inflammatory protein-1 [5,73,74]. The MIB-MIP [Mycoplasma immunoglobulins (Ig) binding protein-Mycoplasma Ig protease] system which is encoded by two genes specific to mycoplasma has the capability to target and deactivate host immunoglobulins (IgG).…”
Section: Immune System Modulationmentioning
confidence: 99%